(untitled) (Transactions of the Association of European Schools of Planning, 2019)
Migration generates both challenges and opportunities. The magnitude of flows and effects on local resources are rarely equally distributed, indeed, the demographic size and economic strength of arrival cities or regions consistently affect outcomes. The nature of these challenges and opportunities is, therefore, extremely varied. These elements have already structured a network of places, refugee-cities, integration hubs, and transit points that play different roles in the increasing process of human mobility. The paper discusses the role of planners in dealing with refugee crises starting from the experience of a university workshop. This allows for a plea in favour of a different approach to planning, one that insists on practice, spatial strategies, and implementation. The paper also illustrates a different teaching approach that takes into account the need to integrate different forms of knowledge and disciplinary perspectives.